Comparison Between Domestic and Hostile Applications of Wireless Sensor Networks - Salwa El-Morsy (Computational Algorithms and Numerical Dimensions)
Man has been benefited a wholesome with the idea of sensors. Sensors not only help us in gathering data, but also provide us a solution to many unsolvable problems. Applicating them over a wide area is quite a tough task, Hence the idea of Wireless Sensors Networking has been introduced. This idea has boosted the success rate of different experiments in the fields of health, Finance, Security, etc. where simple factors like temperature, motion, smoke, pressure etc. are used to muster the required data. These Wireless sensors are basically connected and are allowed to share their information over a network which indeed is connected to the main data center. Simply said this accumulation of sensors wirelessly has provided immense advantage for today’s era. Sensors have extended the sustainability of mankind by making work easy in both domestic and hostile environments.